Clinico-Epidemiological Features of Patients of Acute Pancreatitis with and Without Biliary Ascariasis - Dhar, Suman; Mirjada, Rashed; Waez, Md Shakeel; Chowdhury, Bidhan Roy; Chowdhury, Farhana Hoque; Ahmed, Farid Uddin (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Ascarial invasion of the biliary tree is a well known entity and Pancreatitis is a complication of it. Many recent reports suggest ascariasis induced Acute Pancreatitis (AP) in the tropics, especially in several parts of Indian subcontinent including Bangladesh. This issue has not been well studied in our setting. The aim of this study was to describe and compare the clinico-epidemiological features of patients of AP with and without Biliary Ascariasis (BA). Materials and methods: This hospital based cross-sectional study was conducted at Chittagong Medical College Hospital (CMCH) from April 2017 to September 2017. Thirty five patients of AP with BA and 35 patients of AP without BA from inpatient Department of Medicine and Department of Surgery of CMCH were conveniently included enrolled in this study. The data included a detailed history, clinical examination and investigations with particular references to complete blood cell count, liver function test, serum amylase and ultrasound of the abdomen. Results: Patients with BA were comparatively younger than patients without BA. Females are significantly more (73.4% versus 42.9%) and representation was more from rural area (71.4% versus 49.9%) in BA group than patients without BA. Interval from symptom onset to admission was significantly more in cases of patients without BA in comparison to patients with BA (5.17±1.15 days versus 2.6±1.14 days). Pain was mostly colicky in patients with BA in contrast to patients without BA where the nature of the pain was mostly dull aching in nature. Other features of pain like site, onset, radiation, severity of pain were similar in both groups. History of worm emesis was significantly higher and anorexia was significantly lower in BA group than without BA group. Patients with BA were more anemic than patients without BA,epigastric tenderness was more common in patients without BA than with BA and right hypochondriac tenderness was more common in patients with BA. There was no significant difference in the distribution of the laboratory parameters between two groups. Conclusion: Female patients from rural area with a history of worm emesis and anorexia presented with colicky pain were likely to be a case of AP due to BA. JCMCTA 2020 ; 31 (2) : 99-103